Impact of STEAM activities on climate literacy and creative problem solving skills - Asilturk, Yagmur; Yildirim, Pelin; Kececi, Gonca (Routledge Journals, Taylor & Francis Ltd, 2026)
This study investigates the effects of STEAM activities, aligned with the European Green Deal goals, on climate literacy and creative problem-solving skills of 7th-grade students from a socioeconomically disadvantaged village school in Turkey. A mixed-methods approach was used. A total of 51 students participated, with 27 in the experimental group and 24 in the control group. Over seven weeks, the experimental group engaged in scenario-based STEAM activities, while the control group followed traditional teaching methods. Data were collected using the Climate Literacy Scale, the Creative Problem Solving Inventory, and semi-structured interviews, and analyzed with SPSS 25 and content analysis. Results showed significant improvements in climate literacy and problem-solving skills in the experimental group, while no significant changes were observed in the control group. The study demonstrates that STEAM activities enhance environmental awareness and influence students' career interests in environmental protection. It is recommended to integrate STEAM activities into curricula.
Keywords: Climate literacy; creative problem solving skills; environmental education; secondary school students; STEAM approach